Chhatrapati Shivaji, architect of freedom : an anthology - Kulkarnee, Narayan H. (Chhatrapati Shivaji Smarak Samiti, 1975)
Comprises articles and documents on the influence of the Maharashtrian ruler Shivaji, 1627-1680, on India's national life and literature.